Impact of C-reactive protein and albumin levels on short, medium, and long term mortality in patients with diffuse large B-cell lymphoma. (31st December 2022) - Gradel, Kim Oren; Larsen, Thomas Stauffer; Frederiksen, Henrik; Vinholt, Pernille Just; Iachina, Maria; Póvoa, Pedro; Zampieri, Fernando Godinho; Nielsen, Stig Lønberg; Dessau, Ram Benny; Møller, Jens Kjølseth; Jensen, Thøger Gorm; Chen, Ming; et al.
Abstract: Objectives and study design: In this population-based study of 602 patients, we amended C-reactive protein (CRP) and plasma albumin (PA) levels around the diagnosis of diffuse large B-cell lymphoma (DLBCL) to the International Prognostic Index (IPI) and assessed 0–90, 91–365, and +365-day survival. Results: The CRP did not contribute to the IPI's prognostic or discriminatory ability, regardless of time period, particularly not in models with PA. In contrast, the PA was an important contributor, especially in the 0–90 day period, but also up to one year after the diagnosis. For day 0–90, the model with the IPI only had an Area Under the Receiver Operating Characteristics (AUROC) of 0.742, whereas the IPI with PA as a continuous variable rendered an AUROC of 0.841. Especially the lower PA quartile (18–32 g/L) contributed to the worse prognosis. Conclusions: The amendment of PA to the IPI may significantly improve the short-term prognostic and discriminative ability. Key messages: The amendment of the plasma albumin (PA) level to the International Prognostic Index significantly improved the prediction of mortality up to one year after the diagnosis of diffuse large B-cell lymphoma. It was especially the lower quartile of the PA level (18–32 g/L) that contributed to the worse prognosis.